Interdisciplinary project Feeling the senses: Dressing as an experience - Carvalho, Agda [UNESP]; Trovo, Priscila; Kishimoto, Grace; Rosa, Natalia; Kulaif, Patricia; Valli, Adriana; Braga, Recilene Maia; Da Hora, Miguel; Perez, E. M.; Martinez, E.; DosSantos, FCS (Univ Politecnica Valencia, 2017)
The text provides a discussion of body and dress, to interact with the uncertainties and complexities of a multiple daily life, which is focused on tangible concerns and subjectivities in space. We highlight this experience with the structure that draws the dressing, at the moment when the viscerality of the body is evident, during the perception of the sensory-cognitive aspects. Among the references, the corset, a piece of nineteenth-century women's clothing, whose structure interfered with posture and movement, modeling the silhouette and requesting a corporal organization, which was linked to social and cultural rules of behavior. This project challenges the experience of the female body with the dress, the impositions and current norms, which are often camouflaged or nebulous, but interfered in the experience of the body. This question arises Wearable called Feeling the Senses, research started in 2016, as a proposition which articulates both the process and the implementation, the fields of art, design and technology. Discussion and production comes an interdisciplinary team of researchers, who take part in the research group design and body: projective aspects in art and fashion, coordinated by Agda Carvalho. With an approach focused on the non-linearity of behaviors and the instability of spaces, the structure seeks solutions that blend the rigidity and flexibility of the environment. The materiality and the design simulate a hard aspect, but the corporeal movements expose the unstable situation that surrounds the daily life of the body and the dress. This structure also interferes with posture, movement and body organization, modeling on thebody sillhoutte the social rules, responding to continuous modifications and contemporary reorganizations.
Keywords: Interdisciplinarity; daily life; dressing; corset